Implementasi Nilai-nilai Muhammadiyah dalam Pengabdian Masyarakat di Daerah Terpencil: Studi Kasus di Desa Muzoi, Kecamatan Lahewa Timur, Nias Utara - Hamizan, Muhammad; M. Rofi Zulfikar; Robie Fanreza (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Community service is a manifestation of Muhammadiyah values, especially in 3T areas (Frontier, Remote, and Underdeveloped) such as Muzoi Village, East Lahewa Subdistrict, North Nias. This study aims to analyze the implementation of Muhammadiyah values in community service programs, focusing on education, health, and entrepreneurship. The method used is a case study with a descriptive qualitative approach through direct observation, interviews, and documentation. The results show that the community service program successfully increased the local community's understanding of the importance of clean and healthy living behaviors, entrepreneurial skills through charcoal briquette-making training, and students' motivation to pursue higher education. Despite challenges such as limited infrastructure and cultural barriers, Muhammadiyah values such as independence and social awareness were well-integrated into the daily lives of the Muzoi Village community. This study concludes that the implementation of Muhammadiyah values contributes positively to empowering communities in remote areas.